2022
DOI: 10.3390/gels8020075
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Calcium Silicate Hydrate Gels with Different Calcium to Silica Ratios and Polymer Modifications

Abstract: Calcium silicate hydrate (CSH) gels, the main binding phases of hydrated cement, are the most widely utilized synthetic materials. To understand the influences of composition and polymers on the reaction kinetics and phase formation, CSH gels with varying Ca/Si ratios and amounts of poly (acrylamide-co-acrylic acid) partial sodium salt (PAAm-co-PAA) were synthesized via a direct method. The CSH gels were characterized through isothermal calorimetry, thermogravimetric analysis (TGA), X-ray diffraction (XRD), Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 72 publications
(97 reference statements)
0
11
0
Order By: Relevance
“…These peaks were due to the evaporation of chemically bound water and the degradation of silicate gel hydrates, which occurred at a higher temperature for the 105 °C cured samples. The intensity and the late degradation of the samples cured at 105 °C show a high initial reaction rate and better crosslinking . Liu et al observed a similar DTG peak temperature between 150 and 200 °C in the study of effects of additives and fillers on properties of SS wood adhesive modified with poly(vinyl alcohol) .…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…These peaks were due to the evaporation of chemically bound water and the degradation of silicate gel hydrates, which occurred at a higher temperature for the 105 °C cured samples. The intensity and the late degradation of the samples cured at 105 °C show a high initial reaction rate and better crosslinking . Liu et al observed a similar DTG peak temperature between 150 and 200 °C in the study of effects of additives and fillers on properties of SS wood adhesive modified with poly(vinyl alcohol) .…”
Section: Resultsmentioning
confidence: 93%
“…The intensity and the late degradation of the samples cured at 105 °C show a high initial reaction rate and better crosslinking. 72 Liu et al observed a similar DTG peak temperature between 150 and 200 °C in the study of effects of additives and fillers on properties of SS wood adhesive modified with poly(vinyl alcohol). 33 For the carbonated SS samples, DTG peaks (Figure 5d,f) below 600 °C were seen between 139 °C and 179 °C for samples postcured at 60 °C and between 136 °C and 284 °C for samples postcured at 105 °C.…”
Section: Modulated Dynamic Scanning Calorimetry (Mdsc)mentioning
confidence: 94%
See 1 more Smart Citation
“…The addition of CSH nanoparticles as nuclei has been successfully used to accelerate the process of the hydration and settling of binder phases in both conventional Portland cement and alternative binders [ 17 , 37 ]. In addition, CSH gels are known as the most widely used synthetic materials [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the importance of the gel/space ratio for the compressive strength of cement composites is noted [ 27 , 28 , 29 ]. The study of the microstructure of calcium silicate hydrate (CSH) gels from theoretical and computational points of view, as well as the fractality of CSH and the evaluation of the mechanical properties and durability of CSH—with particular reference to carbonization and chloride/sulfate exposure—are also important in influencing the mechanical properties and durability of cement-based materials [ 30 , 31 ]. The most recent works of authors who studied the formation of the structure of cement pastes from the point of view of the mechanisms of gel formation and hardening are primarily aimed at the microstructural component of these processes and mechanisms [ 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%